2021
DOI: 10.1259/dmfr.20200391
|View full text |Cite
|
Sign up to set email alerts
|

Parotid gland tumors: comparison of conventional and diffusion-weighted MRI findings with histopathological results

Abstract: Objectives: The aim of this study was to investigate the relationship between pathological classification of parotid gland tumors and conventional magnetic resonance imaging (MRI) – diffusion weighted imaging (DWI) findings and also contribute the possible effect of apparent diffusion coefficient (ADC) to diagnosis. Methods: Sixty patients with parotid masses diagnosed using histopathology and/or cytology were enrolled in this retrospective study. All patients were evaluated using a 1.5 Tesla MRI. Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
1
20
1
Order By: Relevance
“…This may be because PA is rich in myxoid and chondroid tissue stroma and has a larger extracellular space than WT, causing a considerable difference in heterogeneity in the ADC model (37,38). This also verifies the application of ADC values in the quantitative analysis to some extent to differentiate PA from WT (39). FS-T2WI or CE-T1WI combined with ADC can improve the performance of the single-sequence model, consistent with previous studies (17,40,41).…”
Section: Discussionsupporting
confidence: 86%
“…This may be because PA is rich in myxoid and chondroid tissue stroma and has a larger extracellular space than WT, causing a considerable difference in heterogeneity in the ADC model (37,38). This also verifies the application of ADC values in the quantitative analysis to some extent to differentiate PA from WT (39). FS-T2WI or CE-T1WI combined with ADC can improve the performance of the single-sequence model, consistent with previous studies (17,40,41).…”
Section: Discussionsupporting
confidence: 86%
“…In previous DWI studies, significant differences in ADC values were reported between benign and malignant head and neck tumors, including salivary gland tumors 18 . Also, it was reported that T2 SI is lower in Whartin tumors and malignant parotid tumors 8 . The morphological features of PGTs can be evaluated by MRI, but detecting the lesions and defining the features may not be sufficient to avoid a biopsy.…”
Section: Discussionmentioning
confidence: 95%
“…We could not find any significant association between malignant and benign lesions in terms of deep or superficial lobe localization. It was previously reported that the tumor heterogeneity and T2 hypointensity may indicate malignancy, and it is not sufficient for precise differentiation 8 . Our results revealed that the T2 SI of the Warthin tumors was significantly lower than that of the pleomorphic adenomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classification of PGTs is hampered by the diverse variations in their histopathology. Presurgical determination of benign or malignant PGTs involves two main methods: fine needle aspiration cytology (FNAC) [ 4 ] and imaging modalities [ 5 ]. Although preoperative FNAC examination can improve the diagnostic accuracy, its use in the diagnosis of PGT is controversial.…”
Section: Introductionmentioning
confidence: 99%